(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction Nurses played an important role in nursing services to infected patients in the covid-19 pandemic and considering the unknown nature of the virus and the shock of the pandemic, its psychological aspects have been less investigated. Therefore, the present study was conducted to investigate effect of spiritual health on the quality of nursing care for patients with covid-19. Methods The present study was done in a cross-sectional-analytical method in the Covid departments of Peymaniye Hospital in Jahrom city in 2021. Sampling was done by census method among the nurses working in the care departments of patients with covid-19. If any nurse suffered from any psychological disorder(s) or didn’t fill in the questionnaire completely, she was classified as exclusion criteria. Demographic form, spiritual health and quality of nursing care questionnaires (QUALPAC= Quality Patient Care Scale) were used to collect necessary data and the findings were analyzed by SPSS version 21. Results The spiritual health score average of the employed nurses was 92.68±15.98. Based on the leveling of the questionnaire, the level of spiritual health of the majority of nurses was at a mean level (60.8%). Also, the findings of the Spearman test indicated that there is a significant relation between spiritual health and the quality of nursing care (r=0.44, P<0.0001). Conclusion Considering the relation between spiritual health and the quality of nursing care, it is recommended that spiritual health services be integrated in the provision of general treatment and care in all hospitals of the country and personnel training should be taken into consideration, too. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 463-470